Effect of the Compaction Pressure and Ni Content on the Modified Aluminum-Based Perovskite Synthesis Designed to Immobilize the Radioactive Waste in Combustion Mode; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Tarasova E. S. Ekaterina Sergeevna; Dolmatov O. Yu. Oleg Yurevich; Isachenko D. S. Dmitry Sergeevich; Permikin A. A. Anton Andreevich; Semenov A. O. Andrey Olegovich (2016, 2016)
Title screen